Review Analysis of Psychological Dynamics and Education of Children as the Victims of Divorce Circumstance - Efendi, Hosin; Prasetiya, Benny; Soliha, Imro Atus (Universitas Muhammadiyah Metro, 2020)
This study examined the factors of divorce and children’s psychological condition of and religious education of children as the victim of divorce circumstance and the impact of parental divorce on the children. This research used the qualitative method. The researcher used observation, interviews, and documentation in collecting the data. The technique of checking the validity of the data used was the triangulation technique. In this study, the triangulation technique used was source triangulation. The data analysis used is descriptive qualitative. The research results on the causes of divorce in Wonomerto Subdistrict exactly at Wonorejo village were due to lack of economic problems. The husband had an affair with other women. Divorce would change the status and roles between husband and wife. A husband would be a widower, while a wife would be a widow. Divorce also impacts children's psychological and religious education in terms of children's psychology, such as changes in children's attitudes and behavior. The child was often angry, embarrassed, insecure, and many others. In terms of religious education, children were also found many difficulties, and it happened because no one encourages, supports, and gives advice anymore to them.